THE EFFECT OF FINANCIAL COMPENSATION AND WORK ENVIRONMENT ON AUDITOR PERFORMANCE AT THE INSPECTORATE OF LHOKSEUMAWE CITY AND BIREUEN DISTRICT - Ilham Satria, Dy (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to examine the effect of financial compensation and work environment on the performance of auditors (a case study on the district government inspectorates of lhokseumawe and bireuen), both individually (partial) and jointly (simultaneously). The research approach uses a quantitative approach and the time horizon used is a longitudinal study. Sources of data collection are primary data and secondary data with the Likert scale method and using a media questionnaire. The data analysis technique used in this research is multiple linear regression analysis technique. Based on the results of the analysis, it can be concluded that financial compensation and work environment have a positive and significant effect on auditor performance, both individually (partial) and jointly (simultaneously).